Réponses

Meilleure réponse !
2014-09-07T20:50:31+02:00
B = (7/3 - 3/2) + [(2 - 3/4) - (3/5-4/7)]
B = ((7 x 2 / 3 x 2 - 3 x 3 / 2 x 3) + (2 x 4 / 1 x 4 - 3/4)) - (3 x 7 / 5 x 7 - 4 x 5 / 7 x 5))
B = ((14/6 - 9/6) + (8/4 - 3/4) - (21/35 - 20/35))
B = 5/6 + (5/4) - (1/35)
B = 5 x 140 / 6 x 140 + 5 x 210 / 4 x 210 - 1 x 24 / 35 x 24
B = 700/840 + 1050/840 - 24/840
B = 1726/840
B = 2 x 863 / 2 x 420
B = 863/420

C = 1/2 × (- 4/3) × (- 3/2)
C = -4/6 x - 3/2
C = 12/12
C = 1

D = - 4/3 + 7/2 - 3/4 - 7/4 - 5/2
D = - 4 x 4 / 3 x 4 + 7 x 6 / 2 x 6 - 3 x 3 / 4 x 3 - 7 x 3 / 4 x 3 - 5 x 6 / 2 x 6
D = - 8/12 + 42/12 - 9/12 - 21/12 - 30/12
D = - 26/12
D = 2 x - 13 / 2 x 6
D = - 13/6

E = 1/2 × - (12/6)

E = 12/12
E = 1